Pontos quânticos de carbono (CQDs) com atividades fluorescentes para aplicações analíticas com imagens digitais - RESQUE, Ian Santana (2019)
On reserch, carbon quantum dots (CQDs) were synthesized, their fluorescence was applied to the detection of sodium hypochlorite using the digital image analysis method (DIA). Synthesis conditions were studied, such as composition, procedure, temperature and time to obtain CQDs with good fluorescent signal. These were synthesized from the composition of citric acid and ethylenediamine on the molar ratio of 1: 1, with glycerol as the solvent, by the two step procedure and the optimum temperature and time of 180 °C and 90 minutes, respectively. The detection of NaClO was by the inhibition of the fluorescence of the CQDs, as measured by the RBG primary color model as an analytical signal for the construction of the calibration curve. The images were obtained by a smartphone and the values of Red (R), Green (G) and Blue (B) were obtained by the image J software and used linear regression to obtain the equations of the line. The calibration curve was constructed with a solution of CQDs in the optimal condition of 6.0 mg L-1 at pH 4 with 0.02 mol L-1 KH2PO4 and dynamic NAClO range of 51 to 242 nmol L-1. The most sensitive analytical curve was the vector calculation with an equation Vector (R, G, B) = 214 (± 20.6) * [NaClO] + 5.2 (± 3.3) with a R2 = 0.991, limit of detection and quantification of 13 nmol L-1 and 43 nmol L-1, respectively. The coefficient of variation for the white measurements was 3.58%, 1.23%, 0.49% and 0.35% for the R, G, B and vector (R, G, B), respectively. These results show that there were few experimental errors and little analytical signal noise.